A SYSTEMATIC REVIEW ON IMPACT OF GREEN MARKETING ON PRODUCT BRANDING AND MARKETING - Uprikar, Dr. Vijay Nagorao (The journal of contemporary issues in business and government, 2023)
Green marketing is an emerging field of research that has been gaining momentum over the past few years. The aim of this study was to perform a systematic review on the impact of green marketing on product branding and marketing. The purpose of this review is to determine the effect of green marketing on product branding and marketing. The review includes studies that have been published in peer-reviewed journals and reports from non- governmental organizations (NGOs) or other sources. the study concluded that green marketing is a powerful tool that can be used to increase sales and brand awareness. Green marketing has the potential to improve the bottom line of companies by reducing costs, increasing profits and raising brand equity.